Ho Chi Minh’s thought on Education and its Significance for the Career of Education in Vietnam Today - Tran Thi Ha (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
One of the most profound and enduring legacies Ho Chi Minh bestowed upon our nation is his thoughts on education, especially in moral education. His educational philosophy is characterized by deep and comprehensive insights, addressing not only the fundamental role and objectives of education but also the content, methodology, and approach to teaching. Ho Chi Minh emphasized the cultivation of knowledge alongside the development of moral character, integrating humanistic values that underscore the importance of educating individuals to become knowledgeable and ethically grounded members of society. His teachings continue to resonate today, serving as both a theoretical framework and a practical guide for shaping educational policies and practices in modern times. These ideas reflect a timeless vision that places equal importance on intellectual and moral development, ensuring that education contributes to the holistic betterment of individuals and the nation as a whole.